2020
DOI: 10.1097/qai.0000000000002250
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Discontinuation of Integrase Inhibitors (INSTIs) in a Large Cohort Setting

Abstract: Background Despite increased INSTI use, limited large-scale, real-life data exists on INSTI uptake and discontinuation. Setting International multicohort collaboration. Methods RESPOND participants starting dolutegravir (DTG), elvitegravir (EVG) or raltegravir (RAL) after 1/1/2012 were included. Predictors of INSTI used were assessed using multinomial logistic regression. Kaplan Meier and Cox proportional hazards models describe time to and factors associated with discontinuation. Results Overall, 9702 persons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 40 publications
(21 reference statements)
4
15
1
Order By: Relevance
“…From 2014 onwards, INSTI-based regimens already accounted for the majority of initial treatments resulting in a maximum of 86% in the year 2017. We found a higher risk for modification on RAL compared to EVG and DTG, mainly due to therapy simplification, which is comparable to previous studies [ 27 , 28 ]. Furthermore, we found that patients who received INSTI-based regimens as their first-line treatment had the highest probability of an undetectable viremia after 12 months.…”
Section: Discussionsupporting
confidence: 89%
“…From 2014 onwards, INSTI-based regimens already accounted for the majority of initial treatments resulting in a maximum of 86% in the year 2017. We found a higher risk for modification on RAL compared to EVG and DTG, mainly due to therapy simplification, which is comparable to previous studies [ 27 , 28 ]. Furthermore, we found that patients who received INSTI-based regimens as their first-line treatment had the highest probability of an undetectable viremia after 12 months.…”
Section: Discussionsupporting
confidence: 89%
“…Previous findings within RESPOND [20] have confirmed that INSTI toxicity only accounts for approximately 5% of the reasons for INSTI discontinuations, similar to findings from the Swiss cohort study [21]. Likewise, a recent, large online-questionnaire examination from the Brazilian Ministry of Health found that only 2.2% of participants experienced self-reported dolutegravir toxicity.…”
Section: Virologic Outcomessupporting
confidence: 73%
“…Treatment‐limiting neuropsychiatric adverse events occurred in about 3.5% of DTG recipients in cohort studies [36], more frequently with DTG ( vs . other INSTI) [37‐40], and with greater frequency in women, those aged 60 years and over, and DTG/ABC co‐administration in one study [37] but not others [38,39].…”
Section: Discussionmentioning
confidence: 99%